Reissues, Rewrites and Political Practice: Rodolfo Walsh in 1973 - Sylvia Saítta (Iberoamericana. América Latina - España - Portugal, 2019)
In 1973, Rodolfo Walsh finishes Operación masacre, a written text, edited several times, rewritten, corrected and completed over seventeen years; publishes Un oscuro día de justicia, a story from 1967; and edits Caso Satanowsky, an investigation from 1958. This article argues that, with these three reissues, Walsh intervenes elusively, but at the same time precisely, in the problems that mark the year: the return of Juan Domingo Perón, the revolutionary struggle, the power of the intelligence services, the performance of the parastatal and parapolitical armed groups, the power of the written press and the cinema through their links with the State.